PREDICTING AFFORDABLE LOSS BEHAVIOR USING THEORY OF PLANNED BEHAVIOR FOR SME OWNER IN JAKARTA GREATER AREA, INDONESIA - Selamat, Frangky; Maupa, Haris; Taba, Muhammad Idrus (International Journal of Application on Economics and Business, 2024)
Entrepreneurs can take affordable loss actions when facing uncertain situations. This action is the entrepreneur's ability and willingness to lose or suffer losses from the entrepreneurial investment he makes. This behavior allows entrepreneurs to survive and even develop when facing an economic crisis due to the past Covid-19 pandemic. This study investigates the variables that influence the affordable loss behavior of SME owners in Jakarta, Greater Area using The Theory of Planned Behavior. Questionnaires were distributed to 200 SME owners engaged in the culinary, retail, service and manufacturing sectors. Data were analyzed using Partial Least Square. The results of this study indicate that attitudes and perceived behavioral control can be used to predict affordable loss behavioral intentions. Meanwhile, the subjective norm variable has insignificant predictive ability. The perceived behavioral control variable has the strongest association with behavioral intention. Entrepreneurs are encouraged to have positive views and attitudes towards their abilities and skills in order to be able to behave at an affordable loss, so that business continuity can be guaranteed.